2015
DOI: 10.1155/2015/628368
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Phosphatase in Stem Cells

Abstract: Alkaline phosphatase is an enzyme commonly expressed in almost all living organisms. In humans and other mammals, determinations of the expression and activity of alkaline phosphatase have frequently been used for cell determination in developmental studies and/or within clinical trials. Alkaline phosphatase also seems to be one of the key markers in the identification of pluripotent embryonic stem as well as related cells. However, alkaline phosphatases exist in some isoenzymes and isoforms, which have tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(118 citation statements)
references
References 94 publications
(94 reference statements)
4
107
0
4
Order By: Relevance
“…Although abundantly present in tissues, the regulation of alkaline phosphatase expression changes due to different factors according to cell type. 24,42,43 It has to be noted that PSI-ALA-Hex upon activation gives rise to the production of formaldehyde. Although participating in fundamental biological pathways in cells, the excessive amounts of formaldehyde have toxic effects by inhibiting cell proliferation and leading to apoptosis through the upregulation of tumor suppressor genes p53 and p21 responsible for the cell cycle regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although abundantly present in tissues, the regulation of alkaline phosphatase expression changes due to different factors according to cell type. 24,42,43 It has to be noted that PSI-ALA-Hex upon activation gives rise to the production of formaldehyde. Although participating in fundamental biological pathways in cells, the excessive amounts of formaldehyde have toxic effects by inhibiting cell proliferation and leading to apoptosis through the upregulation of tumor suppressor genes p53 and p21 responsible for the cell cycle regulation.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the pluripotent characteristics of transduced cells, ESC-like cell clumps were test using the AP assay. AP activity is frequently used to distinguish stem cells from feeder cells as well as from parental cells in reprogramming (Stefkova et al, 2015). The results showed that ES-like colonies expressed high activity of AP, in contrast to MEF feeder cells which show no AP activity.…”
Section: Discussionmentioning
confidence: 99%
“…studies using the alkaline phosphatase inhibitor I-pBTM have demonstrated [47]. It is not clear whether those high levels of alkaline phosphatase in the stratum intermedium are exclusively due to their role in phosphate transport or in the generation of phosphorylated macromolecules as alkaline phosphatase also plays a role in stem cells and is often used as a stem cell marker [48].…”
Section: P63 As a Marker For Epithelial Stem Cells In The Enamel Organmentioning
confidence: 99%